Environmental Awareness and The Role of Public Accounting Professional Bodies in Indonesia: A Brief Reflection (Issues in Social and Environmental Accounting (ISEA), 2014)
This study aims to give an insight about environmental awareness from public accountant and the role of Indonesian accounting professional bodies in ensuring professional sustainability. A naturalistic method was applied to get deep understanding about the perspectives of the boards of professional bodies as a representation from the condition of public accountants in general. Data collection methods used in this study were interviews and focus group discussion. The findings highlight a variety of perspectives on knowledge of environment, interest in environmental accounting and moral responsibility on environmental damage. This variation shows different levels of awareness and it is mainly caused by the lack of law enforcement and no mandatory standards on environmental issues. This condition will threat legitimacy of accounting profession and finally, be able to endangered professional accounting sustainability. Limitations are about the scope and sample,which provide insights of the boards of public accountant professional bodies on environmental accounting issues. Future studies should be done on other accounting fields such as environmental audit, environmental accounting and reporting and environmental costing